Las tics y su incidencia en la comunicación intra institucional del Gobierno Provincial del Guayas - Peralta Castro, Jenny Teresa (2014)
The project must as objective determine the incidence of the use of the TICS in the intra-institutional communication of the Provincial Government of the Guayas. This project is divided in several chapters, so that first it describes in his totality the problem to investigate. The second chapter the antecedents of the investigation and the theoretical fundamentación of the TIC and the enterprise communication are mentioned. Third chapter the methods are exposed to use that they were the deductive one, descriptive and statistical; population and shows; the techniques and instruments of data collection obtained of surveys; finally the presentation of the results statistical tables and graphs were used……